Pengaruh Penambahan Tinja Sapi Sebagai Campuran Dalam Pembuatan Batu Bata - Gobhe, Devikarlinda; Suku, Yohanes Laka; Radja, Veronika Miana (TEKNOSIAR, 2023)
This research aims to use cow feces as a mixture for making bricks. cow feces is added at 0%, 25%, 50% and 75% of the total planned weight of the mixed material, the finished bricks are then tested for compressive strength and absorption capacity based on SII-0021-1978 standards andSNI 15-2094-2000. The research results showed that the compressive strength of bricks without and with the addition of cow feces met the SII-0021-1978 standard but did not meet the standardSNI 15-2094-2000. The absorption capacity of bricks with the addition of 0% and 50% cow feces does not meet SNI 15-2094-2000 standards, while the addition of 25% and 75% cow feces does.